Nosocomial catheter-associated urinary tract infections in the intensive care unit - Luis Alberto Santos Pérez; Cándida Grisel Milián Hernández (Acta Médica del Centro, 2009)
The result of a cross-sectional descriptive study, which included in a prospective form 409 patients admitted in the intensive care unit of the Arnaldo Milian Castro Provincial University Hospital during the period from June 1st 2004 to May 31st 2005, are presented. The urinary tract infections related to the use of urethral catheters were studied with the aim of determining their incidence and the most prevalent microorganisms, and establishing a sequential comparison for similar studies in the future. A total of 409 patients were studied; 304 (74%) had a urethral catheter and seven (2.3%) suffered from a urinary tract infection. The accumulated incidence was 2.3 per every 100 risk patients hospitalized for more than 24 hours, and the density of incidence was 4.6 per every 1.000 days. The isolated germs were: Pseudomonas (42.8%), and Klebsiella, Citrobacter, Proteus y Escherichia coli each one in a case respectively.